Physico-chemical characterization of some beta blockers and anti-diabetic drugs - potentiometric and spectrophotometric pKa determination in different co-solvents - Narasimham, Lakshmi; Barhate, Vasant Dnyandeo (European Journal of Chemistry, 2011)
In the present study we have determined the fundamental physico-chemical properties such as, ionization constant (pKa) and lipophilicity (log P) of some b-blockers and anti-diabetic drugs. The apparent ionization constant (psKa) of selected drugs were determined using potentiometric titration in various co solvent-water mixtures (methanol, ethanol, acetonitrile and dioxane) at different temperatures (25 to 45 °C) and ionic strengths (0.15 to 0.5 M). Effect of temperature, ionic strength and dielectric constant on dissociation constant has been compared. The aqueous pKa values were then obtained by Yasuda-Shedlovsky extrapolation. In the case of water-soluble drugs (Amiloride hydrochloride, metoprolol tartrate and propranolol hydrochloride), the extrapolated results were in good agreement with that of pKa values measured in aqueous solutions under the same experimental conditions, while for the water insoluble drugs (atenolol, amlodipine besylate, gliclazide, glipizide, glibenclamide and pioglitazone), the extrapolated results were in good agreement with the literature values. For few of the selected drugs, the psKa was determined spectrophotometrically and the results were compared with that of potentiometry in various co solvent mixtures. The measured log P values of selected drugs showed acceptable range to that of literature values.